(untitled) (Scientific journal of the Fergana State University, 2023)
Information about the results of pedagogical and scientific analysis of physical, medical-biological, psychological preparation of students of Fergana general secondary schools using special mathematical-statistical methods is presented. The purpose of our research is to test the practical application of the method of canonical values in studying the interdependence of children’s physical and motor skills, as well as to determine the canonical values and canonical correlations between the indicated groups..